1969
DOI: 10.1109/tap.1969.1139479
|View full text |Cite
|
Sign up to set email alerts
|

Monopole and conic antennas on spherical vehicles

Abstract: where the 1~0~ma1iz:ttior~ quantities are given by = I, -&, d o = X.$, a,nd x = h/ko. APPESDIX I1 DERIYATIOK OF THE RADIATIOS PATTERSS OF THE CYLISDRICAL Gap Als~~ssa From ( 5 ) and (6 ) the z component of the electric field for a thin gap is given by If \\-e now asymptoticall-expand the Hankel funct,ion in (24) and substitute ( 2 5 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The frequency of operation is chosen to be 915 MHz corresponding to a wavelength of l ¼ 0:328 m: This results in a D ¼ 0:0152l: We calculate the radiation pattern for two values of sphere radius and compare our results with those reported in [3]. Note that in [3], results are also compared with those reported in [2] and they are shown to be in nearly perfect agreement. As seen from Figures 3 and 4, a very good agreement is observed for both radii despite the existence of the stair-casing errors occurring in modeling the sphere.…”
Section: Comparison With Previous Workmentioning
confidence: 93%
See 2 more Smart Citations
“…The frequency of operation is chosen to be 915 MHz corresponding to a wavelength of l ¼ 0:328 m: This results in a D ¼ 0:0152l: We calculate the radiation pattern for two values of sphere radius and compare our results with those reported in [3]. Note that in [3], results are also compared with those reported in [2] and they are shown to be in nearly perfect agreement. As seen from Figures 3 and 4, a very good agreement is observed for both radii despite the existence of the stair-casing errors occurring in modeling the sphere.…”
Section: Comparison With Previous Workmentioning
confidence: 93%
“…Nearly 40 years ago, with the advent of digital computers, radiation properties of wire and conical antennas mounted on a conducting sphere were computed [1][2][3]. The motivation for these studies was to characterize antennas on space probes and satellites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An FM radio receiver is by far the most common device in commercial vehicle, and its performance of good signal reception is dominantly determined by an antenna, which is generally a monopole that protrudes outside the vehicle [1]. Recently, to improve the durability and appearance and to reduce the wind noise of a pole-type FM antenna, an internal on-glass antenna that is directly printed on a rear or a quarter window has been widely adopted by newer sedan models [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Emission field strengths from cellular phones can occasionally be higher than expected at greater distances and lower than expected at lesser distances. Some experimental studies on the interference between cellular phones and medical devices have been reported in the literature [1][2][3][4][5][6][7]. However, only a few theoretical studies on the evaluation of EMI due to the interaction between cellular phones and medical devices are reported [8,9].…”
Section: Introductionmentioning
confidence: 99%